Deletion of HP1γ in cardiac myocytes afects H4K20me3 levels but does not impact cardiac growth - El‑Nachef, Danny; Fang, Chen; Kajimoto, Hidemi; Brown, Jeremy P.; Singh, Prim B.; MacLellan, W. Robb (Epigenetics Chromatin, 2018)
Heterochromatin, which is formed when tri-methyl lysine 9 of histone H3 (H3K9me3) is bound by heterochromatin 1 proteins (HP1s), plays an important role in differentiation and senescence by silencing cell cycle genes. Cardiac myocytes (CMs) accumulate heterochromatin during differentiation and demethylation of H3K9me3 inhibits cell cycle gene silencing and cell cycle exit in CMs; however, it is unclear if this process is mediated by HP1s. In this study, we created a conditional CM-specific HP1 gamma (HP1γ) knockout (KO) mouse model and tested whether HP1γ is required for cell cycle gene silencing and cardiac growth....
Keywords: cardiac myocytes; cell cycle; conditional knockout; gene expression